ANALISIS KUANTITATIF RAWAT JALAN KASUS DIABETES MELETUS DENGAN METODA HATTA DI RS JASA KARTINI TRIWULAN IV TAHUN 2015 - Wahyuana Amelia Putri (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2016)
AbstractThis study aims to determine the quantitative analysis of outpatient medical record documents in Jasa Kartini Hospital. The data used is data from outpatient medical records document cases of diabetes mellitus in Jasa Kartini Hospital the fourth quarter of 2015. This type of research is descriptive study with retrospective analysis approach, the research method used is observation, with a total population of 240 documents outpatient medical record fourth quarter 2015 in Jasa Kartini Hospital Tasikmalaya, sampling is done by simple random sampling technique as much as 71 outpatient medical record documents. The study of the 4 components of quantitative analysis showed that the components of patient identification information with the level of completeness of the highest in item medical record number, age, contact person, the data intervention and signature of consent of the patient or legal guardian with a percentage of 100% with the number of 71 documents , while the degree of incompleteness is highest in the item name of the patient with a percentage of 31.0% with the number of 22 documents, components recorded evidence with the level of completeness of the highest in the items of laboratory results, results of radiology, prescription drugs, a certificate of nutrition and a certificate of diagnosis with a percentage of 100 % with the number of 71 documents, while the level of incompleteness highest in report items anamnesa with a percentage of 9.9% with a total of 7 documents, components of the validity of the recording to the level of completeness of the highest in the second item that is a signature and the name of the light with a percentage of 91.5% with the number of 65 documents, while the degree of incompleteness is highest on the second item with a percentage of 8.5% with the number 6 documents, components ordinances noted the level of completeness of the highest in the line item remains with a percentage of 100% with the number of 71 documents, while the level of incompleteness is highest in the item element of a correction of 95.8 68% by number of the document. Conclusions from the study at the Hospital Services Kartini Tasikmalaya indicate that charging document outpatient unallocated 100% complete.Key Words: Quantitative Analysis, Completeness, Medical Record Documents, Outpatient, Diabetes MelitusAbstrakHatta,(2008) menegaskan bahwa analisis kuantitatif dimaksudkan untuk menilai kelengkapan rekam kesehatan yang dimiliki oleh sarana pelayanan kesehatan.Hasil studi pendahuluan dari 7 dokumen kasus DM diperoleh prosentase kelengkapan 42,9% dan ketidaklengkapan 57,1%. Penelitian bertujuan mengetahui hasil analisis kuantitatif yang meliputi kelengkapan identifikasi pasien, bukti rekaman, keabsahan rekaman dan tata cara mencatat.Jenis penelitian deskriptif dengan pendekatan retrospektif.Metode penelitian dengan observasi.Dengan teknik simplerandom sampling diperoleh sampel 71 dari populasi 240 dokumen. Hasil penelitian menunjukkan bahwa 1) komponen identifikasi pasien kelengkapan tertinggi pada item nomor rekam medis, usia, orang yang dapat dihubungi, data tindakan intervensi dan tanda tangan persetujuan (100%), sedangkan ketidaklengkapan tertinggi pada item nama pasien (31%);2) komponen bukti rekaman kelengkapan tertinggi pada item hasil laboratorium, hasil radiologi, resep obat-obatan, surat keterangan gizi dan surat keterangan diagnosa (100%), sedangkan ketidaklengkapan tertinggi pada item laporan anamnesa (9.9%);3) komponen keabsahan rekaman kelengkapan tertinggi pada kedua item yakni tanda tangan dan nama terang (91.5%), sedangkan ketidaklengkapan tertinggi pada kedua item tersebut (8.5%);4) komponen tata cara mencatat kesesuaian tertinggi pada item baris tetap (100%), sedangkan ketidaksesuaian tertinggi pada item unsur koreksi (95.8%). Ketidaklengkapan pencatatan dokumen kasus DM cukup tinggi, hendaknya petugas pelayanan klinis lebih meningkatkan kesadaran dalam melengkapi hasil pelayanan demi tercapainya kualitas informasi medis yang berkesinambungan.Kata Kunci: Analisis Kuantitatif, Kelengkapan Pengisian, Dokumen Rekam Medis, Rawat Jalan